An Analysis of Compound Words in The Novel “The Little Prince” - Aisyah Febriyanti; Eva Meidi Kulsum (Gunung Djati Conference Series, 2026)
This study aims to examine compound words in the novel The Little Prince, focusing on the classification of compound words into compound noun, compound adjective, compound verb, and compound adverb. The research employs a descriptive qualitative approach to analyze and categorize these compound words. The findings reveal that there are 28 compound words in the novel, consisting of 22 compound noun, 4 compound adjective, 1 compound verb, and 1 compound adverb. Based on the analysis, compound noun are found to be the most frequently used and dominant word type in the novel. This indicates that The Little Prince relies more heavily on compound nouns compared to other types of compound words